THE ALPHA GENERATION PERSPECTIVE ON THE USE OF TECHNOLOGY IN FILTERING ACTUAL INFORMATION THROUGH SOCIAL MEDIA - Siti Azizah Puteri (English Language Education Department, Faculty of Teacher Training and Education, Syekh-Yusuf Islamic University (PBI FKIP UNIS), 2023)
This study aims to analyze the Alpha Generation's perspective on the use of technology to filter actual information through social media. Generation Alpha refers to individuals born between 2010 and 2025, who grow up and live in an increasingly connected digital age. In an information-abundant environment, it is important to understand how these young people use technology to access and filter current information. This study uses narrative inquiry. This research was conducted with 3 participants, with an average age of 13-15 years. This research is expected to be able to examine the perspective of the alpha generation in exploring social media to filter actual information. This research aims to help academics, practitioners, and other stakeholders better understand and support young people to deal with the challenges of 'bird' information in today's rapidly developing digital era by providing a deeper understanding of the use of technology and social media in filtering information actual information. This study is grounded in the theory of digital literacy levels proposed by Lankshear and Knobel (2011: 167). The study found three 13-15-year-old children of the Alpha generation, who value accessibility and speed in obtaining information through social media. They value personalization and engage in online conversations, demonstrating critical skills in filtering information, verifying information, and contributing to social change.